Outcome analysis of limited open carpal tunnel release: A prospective study - Chandrashekara Chowdipalya Maliyappa; Mulamoottil Abraham George; Bader Said Khamis Al-Marboi (Journal of Orthopedics, Traumatology and Rehabilitation, 2014)
Background: Carpal tunnel syndrome (CTS) is the most common peripheral compressive neuropathy, involving median nerve at the wrist. Traditionally, three different surgical techniques have been described open or standard, minimal invasive or limited open, and endoscopic surgeries. However, the results of each method are conflicting. The goal of our study was to assess the clinical outcome including complication rates following limited open carpal tunnel release. Patients and Methods: The study included patients with idiopathic CTS undergoing limited open carpal tunnel release surgery. The Boston Carpal Tunnel questionnaire was used to assess the symptom severity and functional status pre and post surgical interventions. Results: Twenty two patients (27 hands) underwent limited open carpal tunnel release, and all patients completed the questionnaire. The mean age of patients was 44.9 years with a mean duration of follow-up was 16.2 months. The average surgical wound length (scar length) was 2.7 cm. The median time to return to work was 14 days (range: 7-31). There was a significant improvement in pre to post operative symptom severity score (SSS) and functional status score (FSS). The statistical correlation was significant between pre and post operative SSS and FSS scores. One patient had a superficial infection which was treated conservatively. No patient had pillar pain, scar tenderness, and nerve injuries. Conclusion: The limited open carpal tunnel release surgery is the simple, safe, and effective mode of treatment.